Health-education and the demand for tobacco in ireland, 1953-76 - note - Walsh, BM (Economic & Social Studies, 1980)
THE publication of the report by the Royal College of Physicians in 1962 linking cigarette smoking and lung cancer led throughout the western world to mounting pressure to curb the smoking habit. In Ireland the cancer scare received widespread press coverage, television advertising was phased out by 1971, a warning is now printed on all cigarette packages, and there have been several publically-financed anti-smoking publicity campaigns. Figures for tobacco "retained for home use" per capita (see Table 1) show no long-run trend and might be interpreted as indicating the success of the various measures that have been taken to discourage smoking. More systematic evaluation is, however, required to net out the effect of health education measures. The only study that has addressed this issue is O'Riordan (1969), which was confined to the years before 1968 and found little evidence that consumption had fallen as a result of the cancer scares.
Keywords: Economics; Sociology